Moderating Effect of Self-efficacy for the relationship between participation intention and practice effect - Yu Kang; Yoon Fah Lay (Human Resource Management Academic Research Society (HRMARS), 2025)
Educational practice has always been an important part of teacher education. It not only embodies the organic combination of theory and practice but also serves as an important means to achieve the existing training goals of schools and meet the needs of society. This research has grasped the core connection between "subjective initiative" and "objective effect" in educational practice. From the perspective of students, it focuses on exploring the relationship between students' participation intention, self-efficacy, and practical effect. The moderator of self-efficacy indicates that self-efficacy will affect the actual impact of participation intention on practice effect. To evaluate the measurement and structural models, structural equation modeling (SEM) was performed using the Partial Least Squares (PLS). The findings are displayed: (1) Participation intention positively predicts the practice effect; (2) Self-efficacy moderates the relationship between participation intention and practice effect. From the perspective of students participating in educational practice, this research explores the relationship between students' participation intention, self-efficacy, and practice effect, and mainly explores the moderating role of self-efficacy for the relationship between participation intention and practice effect. Additionally, this research enriches the current understanding of the factors affecting the practice effect and suggests possible directions for future research.